PEMANFAATAN BAHAN SEBAGAI KESIAPAN MENJADI QUALITY CONTROL CUTTING DI GARMEN - Weny Dwi Irawan; Cucu Ruhidawati (Universitas Pendidikan Indonesia, 2015)
Indonesian's garment industry continues to develop, to increase its development, a garment industry needs talented and skillful people, especially for controlling the quality of product, so that the quality control cutting has very important role. The purpose of this study was to obtain the data about learning outcomes of Cutting Analysis and Using Material as the preparation to be a quality control cutting in garment. The method used was a survey method, and the data collection technique was a questionnaire. The respondents in this study were 44 students of Garment Technology and Business class of 2011. The results showed that the respondents have felt the advantages of learning outcomes of Cutting Analysis and Using Material in terms of their competency in applying the concept of Cutting Analysis and Using Material, applying the concept of the review process of cutting, applying the cutting techniques and numbering, and binding, as the preparation for quality control cutting in garment. The conclusion is that more than half of respondents have felt the advantages of the material Cutting Analysis and Using Material class as the preparation to be a quality control cutting in garment presented by lecturer.